A methodology to support the execution of proficiency tests for software quality assessment - Dallilo, Felipe Diniz; Delamaro, Marcio Eduardo; Souza, Simone Senger (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2024: Anais do XXIII Simpósio Brasileiro de Qualidade de Software, 2024)
Consumers often expect our technology products to work perfectly from the first use. However, unlike many physical products whose imperfections are visible and tangible, the software presents a unique challenge. The quest for functional perfection is mitigated by an inherent complexity that often results in unexpected failures.Comparatively, products such as automobiles, household appliances, and even medicines are subjected to rigorous manufacturing and validation processes by laboratories before reaching the consumer. Consolidated methodologies ensure that these products meet pre-defined quality and safety standards.To ensure adequate validation procedures, these laboratories undergo accreditation processes coordinated by regulatory bodies. This activity is known as Proficiency Testing and is applied in several areas, such as Chemistry, Medicine, Forensic Science, among others, with significant academic efforts to improve these procedures.However, in the area of Information Technology (IT), as will be discussed in this work, there is a significant gap. In this context, this article aims to offer a methodological contribution when applying Proficiency Tests to software products. We use Business Process Management and Action Design Research to develop a model adaptable to the dynamism of software products. The proposed model was matured over several Proficiency Tests, where we established a process and supported its execution through computational support that allows structuring, recording, real-time sharing of information, and task automation to apply Proficiency Tests to software products.